2018
DOI: 10.1096/fj.201800284r
|View full text |Cite
|
Sign up to set email alerts
|

SHP2 protects endothelial cell barrier through suppressing VE‐cadherin internalization regulated by MET‐ARF1

Abstract: Vascular endothelial (VE)-cadherin junctional localization is known to play a central role in vascular development, endothelial barrier integrity, and homeostasis. The sarcoma (Src) homology (SH) domain containing protein tyrosine phosphatase (SHP)2 has been shown to be involved in regulating endothelial barrier function; however, the mechanisms remain largely unknown. In this work SHP2 knockdown in an HUVEC monolayer increased VE-cadherin internalization and endothelial barrier permeability. Loss of SHP2 spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 51 publications
3
15
0
Order By: Relevance
“…We found that SHP2 silencing effectively inhibited endothelial cell (BMEC) proliferation (Fig 2G). This effect is consistent with previous observation showing that SHP2 depletion from primary endothelial cells reduces cell proliferation, induce cell death (Mannell et al, 2008), and destabilize endothelial cell junctions reducing endothelial cell barrier functions (Zhang et al, 2019). However, SHP2 depletion from B16F10 cells did not reduce B16F10 cell proliferation (Fig 2G).…”
Section: Inhibition Of Shp2 Tyrosine Phosphatase Compromises Endothelial Cell Viabilitysupporting
confidence: 93%
“…We found that SHP2 silencing effectively inhibited endothelial cell (BMEC) proliferation (Fig 2G). This effect is consistent with previous observation showing that SHP2 depletion from primary endothelial cells reduces cell proliferation, induce cell death (Mannell et al, 2008), and destabilize endothelial cell junctions reducing endothelial cell barrier functions (Zhang et al, 2019). However, SHP2 depletion from B16F10 cells did not reduce B16F10 cell proliferation (Fig 2G).…”
Section: Inhibition Of Shp2 Tyrosine Phosphatase Compromises Endothelial Cell Viabilitysupporting
confidence: 93%
“…These results show that SHP099 reduces endothelial cell proliferation and induces cell death in endothelial cells. Consistent with these results, depletion of SHP2 from primary endothelial cells was reported to reduce cell proliferation, induce cell death (22), and destabilize endothelial cell junctions reducing endothelial cell barrier functions (21).…”
Section: Ephrinb2/shp2 and Ang2/tie2 Activity In Vascular Endothelialsupporting
confidence: 65%
“…Genetic experiments in mice showed that SHP2 is required for the formation of a hierarchically organized vessel network in the mouse yolk sac, linking SHP2 to regulation of post-angiogenic/vasculogenic remodeling events (46). Similarly, the knockout of SHP2 in endothelial cells caused embryonic hemorrhage and death attributed to disruption of endothelial cell junctions (21). Experiments in vitro suggested that SHP2 regulates endothelial adhesive functions and migration stemming from SHP2 binding to the intracellular domain of endothelial platelet-derived growth factor receptor-b (PDGFR-b), VE-cadherin and PECAM-1 (47,48).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations